Pengaruh Religiusitas dan Nilai Stewardship terhadap Motivasi Belajar : Implikasi Etika Profesional Mahasiswa Akuntansi - Alimuddin Alimuddin; Asri Usman; Winda Aulia Syam; Nuraeni Nuraeni (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to provide a comprehensive guide for Master's students in Accounting in conducting a mini research project on the influence of religiosity and stewardship values on learning motivation, as well as their implications for professional ethics. The guide includes a strong theoretical framework, a questionnaire-based quantitative research methodology, and relevant data analysis techniques. Religiosity, as the internalization of religious values, and stewardship values, as an orientation toward collective interests, are hypothesized to influence students’ learning motivation. The learning motivation shaped by these internal values is then analyzed in terms of its implications for the development of professional ethics among accountants. By adopting a multidisciplinary approach and adhering to research ethics standards, this study is expected to contribute significantly to the understanding of character and integrity development in accounting education.